2018
DOI: 10.1101/316398
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical states control visual spatial perception

Abstract: SummaryMany factors modulate the state of cortical activity, but the importance of cortical states for sensory perception remains debated.We trained mice to detect spatially localized visual stimuli, and simultaneously measured local field potentials and excitatory and inhibitory neuron populations across layers of primary visual cortex (V1). Cortical states with low firing rates and correlations between excitatory neurons, and reduced oscillatory activity in Layer 4, accurately predicted single trials of visu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In all tasks, we found that fluctuations in engagement throughout a session correlated with cortical state. Consistent with many prior studies (Busse et al, 2017;McGinley et al, 2015;Pinto et al, 2013;Speed et al, 2018), we found that discrimination of visual or auditory stimuli desynchronizes the corresponding cortical region. However, the desynchronization was global rather than restricted to the sensory region corresponding to the stimulus modality, with the biggest effect in somatomotor cortex for all tasks.…”
Section: Discussionsupporting
confidence: 92%
“…In all tasks, we found that fluctuations in engagement throughout a session correlated with cortical state. Consistent with many prior studies (Busse et al, 2017;McGinley et al, 2015;Pinto et al, 2013;Speed et al, 2018), we found that discrimination of visual or auditory stimuli desynchronizes the corresponding cortical region. However, the desynchronization was global rather than restricted to the sensory region corresponding to the stimulus modality, with the biggest effect in somatomotor cortex for all tasks.…”
Section: Discussionsupporting
confidence: 92%
“…While the most prominent cortical state change occurs upon the transition from sleep to wakefulness (Steriade, 2000;Steriade et al, 2001), the waking period itself is characterized by frequent, and often underappreciated state changes (McGinley et al, 2015b). These waking state fluctuations can profoundly impact sensory-evoked cortical responses and sensory-guided behaviors Engel et al, 2016;Pinto et al, 2013;Sachidhanandam et al, 2013;Speed et al, 2018). In the awake, head-fixed mouse preparation, a frequently used experimental paradigm of waking state fluctuation has been the comparison between periods of stillness and locomotion, particularly in primary visual cortex (V1).…”
Section: Introductionmentioning
confidence: 99%
“…The first trial after the switch of the stimulus location contained a grace period (~1.5 s) where licks to either detector during stimulus presentation were rewarded; thereafter, licks to the wrong detector were unrewarded and penalized with a time-out interval. Details of animal preparation, visual stimulus properties, and behavioral training can be found elsewhere (Speed et al 2018). Each detector was connected to the computer-controlled behavioral apparatus as shown in Fig.…”
Section: Detector Assemblymentioning
confidence: 99%
“…Neural recordings and analysis. Detailed procedures for laminar local field potential recordings have been presented elsewhere (Saleem et al 2017;Speed et al 2018). Briefly, recordings were done with multisite silicon probes (NeuroNexus) consisting of a single 32-channel shank.…”
Section: Detector Assemblymentioning
confidence: 99%
See 1 more Smart Citation